2019
DOI: 10.3390/ijerph16101742
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Distribution of Dengue Virus in Aedes aegypti in Yogyakarta City before Deployment of Wolbachia Infected Aedes aegypti

Abstract: Indonesia is one of the countries where dengue infection is prevalent. In this study we measure the prevalence and distribution of dengue virus (DENV) DENV-infected Aedes aegypti in Yogyakarta City, Indonesia, during the wet season when high dengue transmission period occurred, as baseline data before implementation of a Wolbachia-infected Aedes aegypti trial for dengue control. We applied One-Step Multiplex Real Time PCR (RT-PCR) for the type-specific-detection of dengue viruses in field-caught adult Aedes ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 41 publications
0
15
0
1
Order By: Relevance
“…Many viruses in this study were predominantly ISVs except for BAV, and no arboviruses, such as JEV and DENV, were isolated. Previous studies reported that DENV genomes were detected by RT-PCR in 0.12% (36/29,252) [ 47 ] and 0.66% (110/16,605) [ 41 ] in mosquito population. In a DENV-endemic area in Brazil, the MIR of DENV by RT-PCR in wild Aedes mosquitoes was 19.8 [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many viruses in this study were predominantly ISVs except for BAV, and no arboviruses, such as JEV and DENV, were isolated. Previous studies reported that DENV genomes were detected by RT-PCR in 0.12% (36/29,252) [ 47 ] and 0.66% (110/16,605) [ 41 ] in mosquito population. In a DENV-endemic area in Brazil, the MIR of DENV by RT-PCR in wild Aedes mosquitoes was 19.8 [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…aegypti females collected in periods of high and low arbovirus transmission and tested by RT-PCR [ 30 ] led to estimates of DENV natural infection rate of <1% [ 30 ]. A similarly low DENV natural infection rate from individual mosquitoes was quantified both in Yogyakarta, Indonesia [ 61 ] and, in Ho Chi Minh City, Vietnam [ 62 ]. Particularly for DENV, our study found a similarly low natural infection rate (19/2,161 = 0.87%), in agreement with previous reports and consistent with the low number of reported dengue cases in the city ( S1 Fig ).…”
Section: Discussionmentioning
confidence: 99%
“…DENV-1 was the arbovirus with the highest frequency in the population of infected individuals at 82% (50/61) and the overall infection rate in A. aegypti and A. albopictus was 29.6% (50/169) ( Table 2). The DENV-1 serotype has also been detected more frequently than other arboviruses in Indonesia, Mexico, Cuba, Brazil, and Colombia (Velandia-Romero et al, 2017;Eiras et al, 2018;Garcia-Rejon et al, 2018;Gutiérrez-Bugallo et al, 2018;Rahayu et al, 2019). The high frequency of this arbovirus may be because the transmission in the urban cycle of DENV is provided by the level of viremia of the hosts (humans) since individuals at the beginning of infection have high rates of viremia (Duong et al, 2015;Martínez-Vega et al, 2015).…”
Section: Discussionmentioning
confidence: 99%